Characterization of the LH peak after short and long fixed-time artificial insemination protocols in sheep raised in the tropics - Soriano, Gabriela Azenha Milani; de Ruediger, Felipe Rydygier [UNESP]; Zundt, Marilice; Gomes, Marco Aurélio da Cruz Nobre; de Souza, Lilian Francisco Arantes; Giometti, Ines Cristina; de Paula Nogueira, Guilherme [UNESP]; Zanelli, Gustavo Ricci; de Almeida Rego, Fabiola Cristiane; Castilho, Caliê (Wiley, 2018)
The aim of this study was to evaluate the peak in luteinizing hormone (LH) and the pregnancy rate of sheep (Texel × Santa Inês) in the tropics using short- (6 days) and long-term (12 days) progesterone protocols followed by artificial insemination (AI) both in and out of the breeding season. Experiment 1 was conducted within (IN) the breeding season (autumn, n = 36), and experiment 2 was conducted outside (OUT) of the breeding season (spring, n = 43). In each experiment, the sheep were divided into two groups (6 or 12 days) according to the duration of treatment with a single-use progesterone release vaginal device (CIDR®, Pfizer, São Paulo, SP, Brazil), and blood samples were collected from 10 animals per group every 4 hr to measure the LH and progesterone concentrations. In the spring, the characteristics of the LH peak did not differ between groups; but in the autumn, there were differences between groups at the beginning (G-6 IN: 36.44 ± 5.46 hr; G-12 IN: 26.57 ± 4.99 hr) and end of the LH peak (G-6 IN: 46.22 ± 7.51 hr; G-12 IN: 34.86 ± 8.86 hr). The results showed alterations in the LH peak during the breeding season only in the sheep undergoing the short-term protocol.
Keywords: CIDR; photoperiod; progesterone; radioimmunoassay; Santa Inês